The Analysis of Factors Influencing Behavior of Pregnant Mother in Performing Prevention Mother to Child HIV Transmission (PMTCT) in PHC Pesantren I Kediri - Devy Putri Nursanti; Eri Puji Kumalasari (Journal Of Nursing Practice, 2024)
Background: Mother to child transmission of HIV can be prevented, but the incident of HIV in children from year to year continues to increase. Purpose: The research objective is to analyze the factors influencing behavior of pregnant mothers in performing Prevention Mother to Child HIV Transmission (PMTCT). Method: The research design was analytic observational with cross sectional approach. The population was all of pregnant mothers in working area of PHC Pesantren I Kediri. The samples were 63 respondents using simple random sampling. Data were collected using questionnaires given to pregnant mothers at the time of antenatal care in PHC Pesantren I Kediri and then analyzed using logistic regression. Results: The results showed that variable X1 (role of officer) with p = 0.104; OR = 4.609, Variable X2 (knowledge) with p = 0.004; OR = 31.057, Variable X3 (attitude) with p = 0.030; OR = 8.993, Variable X4 (husband support) with p = 0.015; OR = 4.789, Variable X5 (house distance) with p = 0.720; OR = 1.232 and Variable X6 (interest) with p = 0.014; OR = 2.863. In conclusion, the factors influencing Y (behavior of pregnant mothers in performing PMTCT examination) were knowledge and attitude, with the most dominant factor was knowledge with the influence of 31.057. Conclusion: Shows that,The low level of mother’s knowledge about PMTCT, uncooperative mother’s attitude, lack of husband support and lack of mother’s interest caused the low coverage of PMTCT examination in PHC Pesantren I Kediri. The health promotion efforts need more intensive so that the success of PMTCT program can be achieved.